Ultrasonic flexible microextrusion forming of ZK60 Mg alloy at room temperature. Issue 4 (April 2019) - Lou, Yan; Liu, Xiao
Abstract: A novel method of ZK60 magnesium formed through ultrasonic flexible microextrusion at room temperature was developed. A self-designed apparatus was applied for the ultrasonic flexible microextrusion experiments. The results showed that the forming ability and surface quality of products was improved via ultrasonic flexible microextrusion forming method. The extrusion stress distribution could be more uniform by using ultrasonic plasticizing flexible punch, compared with rigid punch.